Feasibility study of technology footwork ability test on national disability badminton athletes - Fitri, M.; Ali, R. H.; Paramitha, S. T.; Zaky, M.; Sulastri, A.; Apriady, H.; Azhar, M.; Zulnaidi, H. (International Journal of Disabilities Sports and Health Sciences, 2024)
Technological advances in sports testing and measurement are expanding, but there is a notable gap in research focused on physical conditioning tests for athletes with disabilities. This study aims to evaluate the effectiveness of footwork ability test technology for para badminton athletes. A quantitative descriptive design was employed, involving trials with both the footwork ability test technology and conventional methods. The subjects were National Para Badminton Athletes of Malaysia, selected through purposive sampling for their relevance to the research objectives. The study utilized a footwork ability test device, whose validity and reliability were assessed in comparison to conventional tests. Data were analyzed using percentage calculation techniques to determine effectiveness and error rates. Results indicate that the footwork ability test technology achieved an effectiveness rate of 97.1%, demonstrating superior performance with a lower error rate than conventional tests. This indicates the technology's suitability for athletes with disabilities, including those categorized as lower standing, upper standing, and short stature. The findings suggest significant potential for broader application in various sports disciplines. Future research should explore the technology's adaptability to different sports and environmental conditions, contributing to more inclusive and advanced training methodologies for athletes with disabilities.